"The first combat meme brigade of the Slovak internet": hybridization of civic engagement through digital media trolling. Issue 2 (2nd April 2020) - Vicenová, Radka; Trottier, Daniel
ABSTRACT: This paper analyzes a locally bound and hybridized form of civic engagement through digital media. Based on an explorative case study of a Slovak Facebook page called Zomri, engaged mostly in both mockery and denunciation of societal and political actors, the paper aims to challenge existing conceptual definitions of social media-based civic engagements, pointing to its hybridization. Through in-depth interviews with its founders and a survey of its supporters, we position the group and its activities through three separate lenses (trolling, digital vigilantism, and citizen journalism) that constitute an emergent category of dynamic and politically influential civic society actor.